Implementasi Kebijakan Dalam Menyelesaikan Konflik (Studi Di Area Hak Pengusahaan Hutan Tanaman Industri PT. Sinar Mas Grup) Di Kabupaten Pelalawan - Panca Setyo Prihatin; Syaprianto Syaprianto (SISI LAIN REALITA, 2017)
This study aims to see the implementation of policies in resolving conflicts in the area ofIndustrial Plantation Forest Concession Rights of PT. Sinar Mas Group in PelalawanDistrict, the conflict must be quickly resolved so as not to cause greater problems, theseriousness of the government is needed. In this study researchers used theimplementation theory according to Grindle and used qualitative analysis methods withthe aim of describing, analyzing and attempting to elaborate policies and solutions inconflict resolution by interviewing directly and in depth the key informants who wereconsidered most knowledgeable using purposive sampling technique. The findings ofthis study indicate that the implementation of policies in resolving conflicts in the areaof Industrial Plantation Forest Concession Rights of PT. The Sinar Mas Group inPelalawan District has not been implemented properly, so it is expected that thegovernment will be more active in resolving the conflict, one of them is by revising theexisting policy and the government must prioritize the principle of consensus byinvolving the company and community leaders around the company that.